Wild Edible Plants as an Alternative Food Source for The Community of Pakis Baru Village, Nawangan, Pacitan - Cahyanti, Fiky Ariska; Eskundari, Ratna Dewi; Purwanto, Agus (Jurnal Biologi Tropis, 2024)
Wild edible plants" is a term used to refer to wild plants that can be consumed or used as a food source by humans. Village communities often use wild edible plants to obtain additional food sources, especially in situations where access to other food ingredients is limited. The aim of this research is to find out the types of wild plants that are often used as alternative food ingredients, including the parts of the plants used and the processing efforts. The data analysis method used in this research is the qualitative descriptive method. Based on the results of interviews with informants, namely the people of Pakis Baru Village, 37 types of wild edible plants from 22 families were obtained which were used as alternative food, including tubers, vegetables and fruit. The most widely used wild edible plants, namely vegetables (24 species), followed by tubers (6 species), fruits (6 species) and other preparations in the form of grass jelly (1 species). The parts or organs of wild plants consumed are young leaves or leaf shoots, stems, flowers, fruit, bamboo shoots and tubers. The common processing methods are steaming, boiling, sautéing, roasting, botok, extracting the starch for certain food preparations, or consuming it directly as fresh vegetables. The high diversity of wild edible plant species shows that Pakis Baru Village has great potential as an alternative food source. From utilizing this diversity, society can develop varied and sustainable food strategies.